Laccase Immobilization Strategies for Application as a Cathode Catalyst in Microbial Fuel Cells for Azo Dye Decolourization - Mani, Priyadharshini; Fidal, V. T.; Keshavarz, Taj; Chandra, T. S.; Kyazze, Godfrey (Frontiers in Microbiology, 2021)
Enzymatic biocathodes have the potential to replace platinum as an expensive catalyst for the oxygen reduction reaction in microbial fuel cells (MFCs). However, enzymes are fragile and prone to loss of activity with time. This could be circumvented by using suitable immobilization techniques to maintain the activity and increase longevity of the enzyme. In the present study, laccase from Trametes versicolor was immobilized using three different approaches, i.e. crosslinking with electropolymerized polyaniline (PANI), entrapment in copper alginate beads (Cu-Alg) and encapsulation in Nafion micelles (Nafion), in the absence of redox mediators. These laccase systems were employed in cathode chambers of MFCs for decolourization of Acid orange 7 (AO7) dye. The biocatalyst in the anode chamber was Shewanella oneidensis MR-1 in each case. The enzyme in the immobilized states was compared with freely suspended enzyme with respect to dye decolourization at the cathode, enzyme activity retention, power production and reusability. PANI laccase showed the highest stability and activity, producing a power density of 38±1.7 mW m-2 compared to 25.6±2.1 mW m-2 for Nafion laccase, 14.7±1.04 mW m-2 for Cu-Alg laccase and 28±0.98 mW m-2 for the freely suspended enzyme. There was 81% enzyme activity retained after 1 cycle (5 days) for PANI laccase compared to 69% for Nafion and 61.5% activity for Cu-alginate laccase and 23.8% activity retention for the freely suspended laccase compared to initial activity. The dye decolourization was highest for freely suspended enzyme with over 85% decolourization whereas for PANI it was 75.6%, Nafion 73% and 81% Cu-alginate systems respectively. All the immobilized laccase systems were reusable for 2 more cycles. The current study explores the potential of laccase immobilized biocathode for dye decolourization in a microbial fuel cell.